Assessment of Three IAARD Maize Productivity In Tobadak District, Central Mamuju, Indonesia - Marthen Pasang Sirappa; Muhtar Muhtar; Religius Heryanto; Ketut Indrayana; Nurdiah Husnah (JOURNAL OF TROPICAL SOILS, 2021)
Assessment of three IAARD maize productivity was conducted in Tobadak sub-district, Central Mamuju. The purpose of the assessment was to determine the productivity of three IAARD hybrid maize. The area of   study 3 ha, applying Integrated Crop Management (ICM) models. Varieties which assessment Nasa 29, JH 37 and JH 45, and NK 212 as comparison variety. The experiments were arranged in a randomized block design which 3 times replication. Observations were made on the growth and maize yield. Based on the results of mapping of Indonesian Center for Agricultural Land Resources Research and Development (ICALRRD), land suitability classes for maize in Central Mamuju Regency which are quite suitable (S2) and marginal (S3) are 4,308 ha and 87,889 ha respectively, while that not suitability (N) covering an area of 193,441 ha with limiting factors including nutrient retention, nutrient availability, water availability, and root media. The studied was show that IARRD hybrid maize can increase productivity. The results showed that Nasa 29, JH 37, and JH 45 respectively gave yields 12.87 Mg, 9.02 Mg, and 7.77 Mg ha-1, higher than the average maize yield achieved in West Sulawesi and Central Mamuju Regency, each 4.70 Mg ha-1and 5.19 Mg ha-1. Nasa 29 gave higher yields and was significantly different compared to NK 212 (9.65 Mg ha-1) as comparison variety, and JH 37 variety was not significantly different with NK 212, but while JH 45 variety had lower results and was significantly different with NK 212. Nasa 29 and JH 37 varieties have the opportunity to be developed in Tobadak district, Central Mamuju, West Sulawesi.